Evaluating the influence of corporate social responsibility on brand reputation in the mining industry: a case study of Exxaro's Grootegeluk mine - Mashego, Sendra Dimakatso (Marketing, 2021)
Corporate Social Responsibility (CSR) is now playing an imperative role in South Africa and globally, especially in the mining sector. This industry is expected to make profits while contributing towards a better society. Despite the industry‘s significant contribution to the economy, it also has a negative impact socially and environmentally. Over the past decades the mining sector has been seen as not mindful of its immediate stakeholders. Communities in close proximity to mines do not trust mining companies due to perceptions that mining companies fail to consider the environment within which they operate. Communities are often left with the impression that mines have simply degraded the environment without contributing to sustainable local development such as such as poverty, health, infrastructure, education and unemployment. The reputation of mining companies thus has declined, resulting in economic losses. Mining companies still interpret CSR as an environmental stewardship rather than a model for improving alignment with its stakeholders, as well as enhancing and building brand reputation. The purpose of this study is to evaluate the impact of CSR on the mining industry's brand reputation. The study links the CSR efforts of Exxaro‘s Grootegeluk Mine and their ability to enhance the mine‘s reputation in areas of operation. Exxaro is among the top five coal producers in South Africa. The Grootegeluk Coal Mine is an open cast coal mine in Lephalale, Limpopo. A quantitative research methodology was applied using a face to face structured self-administered questionnaire to collect primary data from a sample of 330 participants. Descriptive statistical analysis was conducted with a view to condense the sample composition. The non-probability sampling was deemed appropriate for this study, particularly, the simple random sampling. Regression analysis was deemed suitable to for this study. The collected data was analysed using SPSS version 26.0. Research results have shown that CSR has a favourable association with brand reputation. The study found that community members are more aware of the mine‘s economic responsibility in relation to other dimensions of CSR. This finding implies that the community is more in-tune with aspects that have a direct bearing on their livelihood and are more inclined to seek opportunities and initiatives that improve their overall standard of living. Overall, the findings show that organisations that invest in socially responsible behaviour have higher levels of perceived reputation among the society. Philanthropic initiatives should be developed with the involvement of community members to ensure that their real needs will be determined. Poorly developed community projects do not benefit the mine or the community. The mines should look into sourcing the majority of its staff from the local community. In addition, mining organizations should look into aggressively training local community members who do not possess the required skills necessary for employment within the mining sector. Furthermore, communities should be made aware of all CSR initiatives which are relevant to them through community engagement initiatives because this action will lead to attitude and behaviour changes towards the mine. Previous studies have focused mainly on how CSR initiatives contribute to brand value, customer satisfaction, brand attitude, customer retention, and customer loyalty, and on the relationship between CSR and organization performance. This study highlights the importance of CSR measures on organizational reputation and advises policymakers, the mining industry and scholars.